Designing immersive stories with novice VR creators: a study of autobiographical VR storytelling during the COVID-19 pandemic - Bahng, Sojung; McArthur, Victoria; Kelly, Ryan M. (Frontiers in Virtual Reality, 2023)
This practice-based research project investigates the use of virtual reality (VR) as an autobiographical storytelling device for novice VR creators. Collaborating with university students in Canada, we designed eight individual VR stories that express each student’s experiences of lockdown during the early stages of the COVID-19 pandemic. We conducted interviews with the students to understand how VR contributed to conveying their individual experiences. Our findings demonstrate how immersive VR can be effectively mobilized as a meaningful tool for sharing autobiographical stories related to isolation, loneliness and disconnection from society. Specifically, participants felt that VR helped to convey subjective feelings arising from isolation; that immersion in VR contributed to a sense of confinement and separation from the world; that the creative possibilities within VR enabled them to express their innermost feelings; and that the inclusion of environmental details was crucial for conveying their experience. Our study highlights the potential for VR to be used as an autobiographical storytelling tool and shows how this can be achieved through iterative collaboration between VR experts and novices.